2001
DOI: 10.1074/jbc.m104208200
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Binding Specificity of the Multiple PDZ Domains of INADL, a Human Protein with Homology to INAD from Drosophila melanogaster

Abstract: PDZ domains are protein-protein interaction modules that typically bind to short peptide sequences at the carboxyl terminus of target proteins. Proteins containing multiple PDZ domains often bind to different transmembrane and intracellular proteins, playing a central role as organizers of multimeric complexes. To characterize the rules underlying the binding specificity of different PDZ domains, we have assembled a novel repertoire of random peptides that are displayed at high density at the carboxyl terminus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
83
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(87 citation statements)
references
References 48 publications
4
83
0
Order By: Relevance
“…This idea is lent credence by the findings that PDZ domains can discriminate interaction partners based on single amino acid substitutions (Songyang et al, 1997;Gee et al, 2000;Vaccaro et al, 2001). Therefore, the differences in the PDZ domain-binding C-termini of Kir4.1 (-R-I-S-N-V) and AQP4 (-V-L-S-S-V) may facilitate the preferential binding of AQP4 to a particular syntrophin isoform and Kir4.1 to another.…”
Section: Discussionmentioning
confidence: 92%
“…This idea is lent credence by the findings that PDZ domains can discriminate interaction partners based on single amino acid substitutions (Songyang et al, 1997;Gee et al, 2000;Vaccaro et al, 2001). Therefore, the differences in the PDZ domain-binding C-termini of Kir4.1 (-R-I-S-N-V) and AQP4 (-V-L-S-S-V) may facilitate the preferential binding of AQP4 to a particular syntrophin isoform and Kir4.1 to another.…”
Section: Discussionmentioning
confidence: 92%
“…Several experimental data con¢rm this statement: we have shown that the substitution of the histidine at the crucial position KB1 of hINADL-7 (a class I binding PDZ) is not su¤cient to change its binding speci¢city and to confer a clear ligand preference [1]. Furthermore, the ¢rst PDZ of MUPP1 is a member of the most abundant group (G,H); therefore it should bind to class I motifs.…”
mentioning
confidence: 86%
“…On the other hand, target peptides may be classi¢ed according to the (few) speci¢c residues that constitute the binding motif, through analysis of molecular repertoires (libraries of synthetic peptides; phage display; two hybrid, etc.) that allow identifying collections of di¡erent ligands.We have recently pointed out that, in order to characterize PDZ domains and to infer their binding speci¢city, it is necessary to exploit computational procedures, which simultaneously take into account all the contact positions of the domain binding pocket and the corresponding residues of the ligand [1]. PDZ domains are protein interaction modules that recognize and bind the C-terminal four residues of their target.…”
mentioning
confidence: 99%
“…Although a homologous complex of the fly Signalplex has not been described in ipRGCs, several components of this multiprotein complex seem to be conserved (18). Specifically, a protein homolog of dINAD, INAD-like (INADL), bearing seven PDZ domains, has been identified in humans (46). A search for a functional protein interaction network, performed with the STRING database (Fig.…”
Section: Discussionmentioning
confidence: 99%